College Performance Monitoring Application using Appclay Shephertz - Munawir; Imfrianti Augtiah; Afrizal; Sunardi (International Journal Software Engineering and Computer Science (IJSECS), 2022)
This college monitoring application was developed using Appclay Shephertz by applying 8 Key Performance Indicators for all Colleges. The results of the application have succeeded in displaying data on eight college performance KPIs, namely; 1) graduates get decent jobs, 2) students get experience off campus, 3) lecturers have activities outside of campus, 4) teaching practitioners on campus, 5) lecturers' work is used by the community, 6) study programs work together with class partners world, 7) Collaborative and participatory classes, and 8) international standard study programs. Users can access by pressing the button. Then a black-box test is carried out on this application, the results are that all the buttons tested run well and are ready to be used. This research uses the R&D (Research and Development) development model. To test the success of the Higher Education Performance Monitoring Application, the Higher Education Performance Monitoring Application test was used with 17 test items having a 100% success rate, the Feasibility Test and the Interpretation Percentage were used by experts in measuring aspects of design, communication, and software assessment so that the percentage was 81, 42%, and in the validation test, the provisions on item 25 in the Aiken V table are with a lower limit of 0.64 to an upper limit of 0.93 or a V value of 0.83. The results of the average value of V = 0.794 are declared valid.